One-hundred days of monitoring of patients undergoing hematopoietic stem cell transplantation: events of metabolic syndrome - Spexoto, Maria Claudia [UNESP]; Oliveira, Maria Rita Marques de [UNESP] (My University, 2014)
Objective This study assessed early manifestations of metabolic syndrome determinants in patients submitted to hematopoietic stem cell transplantation. Methods Twenty-seven individuals participated in the study (20 with autologous and 7 with allogeneic hematopoietic stem cell transplantation). Anthropometric variables and biochemical indicators of lipid and glucose metabolism were determined before and 100 days after hematopoietic stem cell transplantation.Results The mean total cholesterol (p=0.086), very low density lipoprotein-cholesterol (p=0.069) and triglycerides (p=0.086) of all patients did not change significantly between the two study periods, but when the patients were separated by type of hematopoietic stem cell transplantation, triglycerides and very low density lipoprotein-cholesterol were close to the critical level of significance for individuals with allogeneic hematopoietic stem cell transplantation (p=0.060) and total cholesterol was significant in individuals with autologous hematopoietic stem cell transplantation (p=0.027). Anthropometric variables did not change significantly between before and 100 days after hematopoietic stem cell transplantation. Conclusion Metabolic syndrome risk factors may be associated with lipid metabolism in the early phase of allogeneic and autologous hematopoietic stem cell transplantation.

Objetivo Este estudo avaliou as manifestações precoces de fatores determinantes da síndrome metabólica em pacientes com transplante de células-tronco hematopoéticas. Métodos Vinte e sete indivíduos participaram do estudo (20 autólogos e 7 alogênicos). Variáveis antropométricas e indicadores bioquímicos do metabolismo glicídico e lipídico foram determinados antes e após 100 dias do transplante. Resultados A média de colesterol total (p=0,086), lipoproteínas de muito baixa densidade-colesterol (p=0.069) e triglicerides (p=0.086) de todos os pacientes não sofreu alteração significativa entre os dois perídos, porém, quando os pacientes foram separados pelo tipo de transplante de células-tronco hematopoéticas, os triglicerídeos e o lipoproteínas de muito baixa densidade-colesterol apresentaram-se próximos do nível crítico de significância para os indivíduos com transplante alogênico (p=0,06) e o colesterol total aumentou significativamente entre os indivíduos autólogos (p=0,027). As variáveis antropométricas não alteraram significativamente na comparação antes e após transplante de células-tronco hematopoéticas. Conclusão Os fatores de risco para síndrome metabólica podem ser associados com o metabolismo de lipídios na fase inicial do transplante alogênico e autólogo.
Cem dias de monitoramento de pacientes submetidos ao transplante de células-tronco hematopoéticas: eventos da síndrome metabólica
Keywords: Body composition; Hematopoietic stem cell transplantation; Lipids; Metabolic syndrome; Composição corporal; Transplante de células-tronco hematopoéticas; Lipídeos; Síndrome metabólica